2020
DOI: 10.3390/ijerph17072605
|View full text |Cite
|
Sign up to set email alerts
|

Placement of Outdoor Exercise Equipment and Physical Activity: A Quasi-Experimental Study in Two Parks in Southern California

Abstract: To reduce the burden of chronic disease, the Centers for Disease Control and Prevention (CDC) funded the Orange County Partnerships to Improve Health (OC-PICH) project in Orange County, California. One of the strategies included adding outdoor exercise equipment (OEE) in two parks in Garden Grove and Anaheim. Using a quasi-experimental pre-post design, we evaluated park users’ physical activity levels before and after OEE installation using the System for Observing Play and Recreation in Communities (SOPARC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…From a land use perspective, teams noted that abandoned property or empty lots could be converted to outdoor fitness areas to promote physical activity. 42 One team further recommended the city invest in “outdoor exercise equipment (OEE) to build healthier communities.” According to Sami et al, 43 the placement of OEE in parks significantly increased physical activity levels among park users. Students observed that an investment in OEE as a preventative health measure would be less expensive than the cost of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…From a land use perspective, teams noted that abandoned property or empty lots could be converted to outdoor fitness areas to promote physical activity. 42 One team further recommended the city invest in “outdoor exercise equipment (OEE) to build healthier communities.” According to Sami et al, 43 the placement of OEE in parks significantly increased physical activity levels among park users. Students observed that an investment in OEE as a preventative health measure would be less expensive than the cost of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…We consider this to be a particularly important point as it has been shown that placing training equipment in certain areas of the park leads to an increase of physical activity level for those who spend time in the park. [28][29][30] It is important to emphasize the role of the trainer in adapting the workouts and creating variety in order to help lead people into a healthier lifestyle. Furthermore, it is known that outdoor gyms usually do not imply the presence of a trainer.…”
Section: Discussionmentioning
confidence: 99%
“…The following supporting information can be downloaded at https: //www.mdpi.com/article/10.3390/ijerph191912590/s1, Supplement File S1: Interventions covered in this study; Supplement File S2: Risk of bias; Supplement File S3: GRADE; Supplement File S4: Tables S1-S3. References [75][76][77][78][79][80][81][82][83][84] are cited in Supplementary Materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%